Accelerating abscission of macadamia nuts using ethephon: are there implications for nut quality? - Aruwajoye, Noluthando Noxolo; Olarewaju, Olaoluwa Omoniyi; Oluwalana-Sanusi, Abimbola E.; Mditshwa, Asanda; Magwaza, Lembe Samukelo; Tesfay, Samson Zeray (Taylor and Francis, 2025)
Macadamia is a valuable nut due to its high content of healthy monounsaturated fats, dietary fibre, antioxidants, and essential minerals such as magnesium-B and potassium. One of the major issues affecting industries around the globe is the delayed nut abscission and a prolonged and expensive harvest. A delay in harvesting also reduces the quality of the kernel. To address this challenge, ethephon is used to accelerate abscission, helping to prevent delays in harvesting. Ethephon can cause up to a 15-fold increase in nut abscission within 4 weeks compared to untreated trees. We provide a brief overview of the use of ethephon and its effects on nut quality. The major side-effects of ethephon used to manage macadamia harvesting are associated with ethylene, which is released from ethephon during the acceleration of plant senescence. This process impacts nut quality and shelf life by modulating lipid composition and nut biochemistry. Additionally, ethephon influences the appearance of the nut and the expression and regulation of specific plant genes. This review bridges the information gap between the application of ethephon for harvesting and its effects on the nut quality.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 3008 Horticultural Production; Prevention; Nutrition; Biotechnology; 3001 Agricultural biotechnology; 3108 Plant biology